Effect of Anticoagulant and Antiplatelet Drugs on Outcome of Arterio-Venous Fistula Created for Hemodialysis Access (Bangladesh Journal of Urology, 2022)
Background: Arteriovenous fistula (AVF) creation is the primary mode of achieving vascular access for hemodialysis in chronic renal failure (CRF). Because of high complication rates like thrombosis, maintenance of the fistula is a major challenge. Although antiplatelet and anticoagulant drugs are emerging rapidly for improving the outcome of AVF but fear of bleeding, hematoma, subsequent compression of AV fistula and blockade restrict their use in many dialysis centers.Objective: To see the effect of anticoagulant & antiplatelet drugs in improving primary patency rate and reducing early thrombus formation of AVF.Methods: This clinical trial was conducted in the Department of Urology Bangabandhu Sheikh Mujib Medical University, Dhaka from November, 2018 to October, 2019. Ninety six ESRD patients who underwent AV fistula with immediate postoperative had thrill and murmur were included as study population as per selection criteria. Informed written consent was taken from all the patients. Patients were divided into two groups using computer generated random number (group I and group II). In group I, patients anticoagulation and antiplatelet drugs were used and in group II, patients anticoagulation and antiplatelet drugs were not used after creation of AVF. Patients were followed up on 3rd POD, at 2 weeks and at 4 weeks after the operation and re-evaluated with clinical examinations and investigations. The outcome were evaluated and compared between two groups.Results: In this study maximum patients were more than 40 years old in both groups. Mean age was 47.89 ± 12.54 years in group I and 46.29 ± 14.78 in group II. Males were predominant in both groups. Male to female ratio was 3.36:1 and 5.8:1 in group I and group II respectively in this study. In this study 35.4% in Group I and 45.8% in Group II patients had hypertension. 47.9% in Group I and 60.4% in Group II patients had DM. Thrombosis was significantly lower in study group (group I) than control group (group II). Primary patency was significantly higher at 4th week after treatment in group I than group II. Bleeding was observed in one (2.1%) patients at 1rd POD in group I who came with emergency & managed conservatively. Haematoma was observed in 1 (2.1%) patients at 3rd POD in group I.Conclusion: Use of antiplatelet and anticoagulant agents prevented the loss of AV patency. But it still needs to be determined whether the potential benefits of anticoagulant & antiplatelet therapy outweights the risk of adverse events.Bangladesh J. Urol. 2021; 24(1): 90-98